Precise motion with piezoelectric actuator. - Giurgea, Constantin. (University of Ottawa (Canada), 2002)
The purpose of this study is to determine the displacement performance of a high accuracy-positioning device equipped with three piezo ceramic actuators. The displacement performance of each individual actuator is investigated in order to perform controlled motion over a very small range. A nanometric precision three-degrees of freedom positioner was designed and fabricated. In order to design a proper closed-loop controller, the open loop characteristics of the nanopositioner were experimentally investigated.
Keywords: Engineering, Mechanical.